2011
DOI: 10.1016/j.cell.2011.09.045
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved SREBP-1/Phosphatidylcholine Feedback Circuit Regulates Lipogenesis in Metazoans

Abstract: Summary Sterol Regulatory Element-Binding Proteins (SREBPs) activate genes involved in the synthesis and trafficking of cholesterol and other lipids, and therefore are critical for maintaining lipid homeostasis. Aberrant SREBP activity, however, can result in excess stored fat and contribute to obesity, fatty liver disease and insulin resistance, hallmarks of metabolic syndrome. Our studies identify a conserved regulatory circuit in which SREBP-1 controls production of the methyl donor S-adenosylmethionine (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
422
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(458 citation statements)
references
References 60 publications
28
422
1
7
Order By: Relevance
“…Knockdown of PCYT1A expression in Caenorhabditis elegans and in human hepatocytes was shown to reduce PC levels, activate SREBP1c, and increase de novo lipogenesis and LD/triacylglycerol accumulation (17). These findings are consistent with the presence of steatosis in liver-specific Pcyt1a knockout mice (18) and in our patients.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Knockdown of PCYT1A expression in Caenorhabditis elegans and in human hepatocytes was shown to reduce PC levels, activate SREBP1c, and increase de novo lipogenesis and LD/triacylglycerol accumulation (17). These findings are consistent with the presence of steatosis in liver-specific Pcyt1a knockout mice (18) and in our patients.…”
Section: Resultssupporting
confidence: 90%
“…insight was recently provided by Walker et al (17) in a series of experiments suggesting that PC levels act as a rheostat for the activation of SREBP1c, a transcription factor known to induce expression of all of the key enzymes involved in fatty acid synthesis. Knockdown of PCYT1A expression in Caenorhabditis elegans and in human hepatocytes was shown to reduce PC levels, activate SREBP1c, and increase de novo lipogenesis and LD/triacylglycerol accumulation (17).…”
Section: Resultsmentioning
confidence: 99%
“…Because the increases of both hepatic CFAM and TAG were closely associated with hepatic PC, it was plausible that the levels of increased TAG by CFAM in our experimental conditions were partly dictated by decreased PC concentrations. Decreased PC levels can trigger the relocation of SREBP‐activating proteases resulting in the activation of SREBP‐1 and transition to the nucleus, and the upregulation of lipogenesis (Walker et al., 2011). However, in the present study, no significant effect of CFAM was noted on hepatic PEMT activity and CT‐α protein, suggesting that the decrease in liver PC levels observed in the present study was independent of PC biosynthesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, as derived from the different tilt angles in MD simulations of different membrane thickness, the flexure of the S2P substrate and all derived consequences will be directly influenced by the characteristics of the lipid membrane. Work by Walker et al concluded from cell biological studies on Caenorhabditis elegans previously that membrane composition and curvature play a significant role for SREBP-1 cleavage in vivo, which could be related to the SREBP flexing (10).…”
Section: Discussionmentioning
confidence: 99%
“…Site-1 protease (S1P) and S2P, located in the Golgi, in turn exert release of the active transcription factor (2). SREBP-1, which is linked to regulation of fatty acid, phospholipid, and triacylglycerol synthesis, can be activated by retrograde transport of the respective proteases from the Golgi into the ER (10). Cleavage of the SREBP precursor molecule arises in two steps.…”
mentioning
confidence: 99%